Alterações clínicas e laboratoriais de equinos submetidos à biópsia hepática com agulha Tru-cut guiada por ultrassom - Queiroz, Daniela Junqueira de [UNESP] (2014)
Liver diseases are very common in livestock animals and are responsible for numerous economic losses, associated not only with death but also with low production rates and expenses with diagnostic exams and treatments. Hepatic diseases in horses are relatively frequent and it can harm animals of all ages, sex and breeds. The diagnosis of liver affections in domestic animals is made with biochemical analyses, x-ray and ultrasound exams, and histopathological exam of liver fragment obtained by a liver biopsy. The aim of this study was to evaluate the possible clinical and laboratorial changes induced by the percutaneous liver biopsy technique guided by ultrasound in horses. Eight adult horses, male or female, ages ranged from 5 to 10 years, were used in this study. The animals were divided into two experimental groups: control group and biopsy group. Peritoneal fluid and blood samples were collected for hematimetric, leucometric and biochemicanalysis, besides the daily physical exams. The analyzed variables did not differ statistically in between the two groups, regardless the peritoneal fluid color witch became reddish after the biopsy was done. In conclusion, the Tru-cut liver biopsy technique is safe and efficient; its use for diagnoses purposes of hospital routine of liver diseases in horses ...